An Incomplete Transition : Overcoming the Legacy of Exclusion in South Africa - World Bank Group (World Bank, Washington, DC, 2018)
South Africa has come a long way since the advent of democracy, but its transition remains incomplete. The first three clauses of the Freedom Charter—the historic 1955 document setting out the central objectives of the democratic movement—were (i) the people shall govern; (ii) all national groups shall have equal rights; and (iii) the people shall share in the country’s wealth. While the first two objectives have largely been achieved since the first democratic elections of 1994, historical disadvantage remains a determinant of income, wealth, and opportunity, notwithstanding some progress. As such, the economic transition from a system of exclusion under segregation and apartheid remains incomplete. This SCD identifies five key constraints. These are (i) insufficient skills; (ii) the skewed distribution of land and productive assets, and weak property rights; (iii) low competition and low integration in global and regional value chains; (iv) limited or expensive spatial connectivity and under-serviced historically disadvantaged settlements; and (v) climate shocks: the transition to a low-carbon economy and water insecurity.